Development of antibacterial nanocomposites by combination of bacterial cellulose/chitin nanofibrils and all-natural bioactive nanoparticles - Yuqi Mei; Yunyi Yang; Ruohang Gao; Mengyue Xu; Qing Li; Zhili Wan; Xiaoquan Yang (Current Research in Food Science, 2023)
In this study, a functional composite membrane was facilely fabricated by using a dual nanofibril system of bacterial cellulose (BC) and chitin (CH) nanofibrils as bio-based building blocks. The BC-CH membranes with enhanced antibacterial activity were constructed by incorporation of all-natural bioactive nanoparticles (GBTPs), which were formed by spontaneous molecular interactions of three naturally occurring active small molecules, i.e., glycyrrhizic acid (GA), berberine (BR), and tannic acid (TA). The microstructure, physicochemical properties, and antibacterial behaviors of the resulting BC-CH-GBTPs nanocomposites were then characterized. The obtained results showed that the GBTPs with a diameter of around 50–100 nm and membrane matrix were bound by non-covalent interactions, and the addition of GBTPs did not compromise the structural integrity and thermal stability of the composites, which retained good mechanical properties. Furthermore, the addition of GBTPs led to a rougher surface structure and increased the water contact angle of the membrane surfaces from 48.13° to 59.80°. The antimicrobial tests indicate that the BC-CH-GBTPs nanocomposites exhibited significant inhibitory effects against Escherichia coli and Staphylococcus aureus, showing a satisfactory antibacterial ability. These results suggest that the BC-CH-GBTPs nanocomposites based on all-natural, plant-based building blocks, hold promising potentials as active packaging materials for sustainable applications.